Visualized effect of oxidation on magnetic recording fidelity in pseudo-single-domain magnetite particles - Almeida, Trevor P.; Kasama, Takeshi; Muxworthy, Adrian R.; Williams, Wyn; Nagy, Lesleis; Hansen, Thomas W.; Dunin-Borkowski, Rafal E. (Nature Publishing Group, 2014)
Magnetite (Fe3O4) is an important magnetic mineral to Earth scientists, as it carries the dominant magnetic signature in rocks, and the understanding of its magnetic recording fidelity provides a critical tool in the field of palaeomagnetism. However, reliable interpretation of the recording fidelity of Fe3O4 particles is greatly diminished over time by progressive oxidation to less magnetic iron oxides, such as maghemite (g-Fe2O3), with consequent alteration of remanent magnetization potentially having important geological significance. Here we use the complementary techniques of environmental transmission electron microscopy and off-axis electron holography to induce and visualize the effects of oxidation on the magnetization of individual nanoscale Fe3O4 particles as they transform towards g-Fe2O3. Magnetic induction maps demonstrate a change in both strength and direction of remanent magnetization within Fe3O4 particles in the size range dominant in rocks, confirming that oxidation can modify the original stored magnetic information.